Absorbable hemostatic yarn and preparation method thereof
By performing multi-step chemical treatment of gauze and the application of modified materials, the existing hemostatic yarns have been solved, and the effects of efficient hemostatic and wound healing are achieved.
Patent Information
- Application Number
- CN202510063786.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-18
AI Technical Summary
The existing absorbable hemostatic yarn has weak antibacterial properties and low hemostatic efficiency, which cannot be suitable for large-scale bleeding.
By alkalizing, acidizing, oxidizing and modifying the gauze, modifying materials such as modified seaweed fibers, carboxymethyl cellulose and modified talc powder are used to improve the hygroscopicity, hemostatic properties and antibacterial properties of the gauze.
It significantly improves the hygroscopicity and hemostasis performance of gauze, enhances antibacterial ability, can quickly stop bleeding and promote wound healing, and is suitable for cases of massive bleeding.
Smart Images

Figure BDA0005243647850000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of biomedical composite materials, and more specifically, to an absorbable hemostatic yarn and a preparation method thereof. Background Art
[0002] Absorbable hemostatic gauze is a surgical product widely used in the medical field, mainly used to control bleeding and promote wound healing. It is usually made of biodegradable materials, such as fibrin glue hemostatic materials, oxidized cellulose hemostatic materials or chitosan hemostatic materials, and is used to stop bleeding in local difficult-to-suture wounds in the human body or animal body. These materials can gradually decompose and be absorbed in the body, without the need for secondary surgery to remove them.
[0003] Oxidized regenerated cellulose is a gauze or cotton-like absorbable hemostatic material made by oxidizing cellulose to become cellulose acid. It has the appearance and texture of cotton yarn, good biocompatibility, biodegradability and non-toxicity. Its hemostatic mechanism is to aggregate the platelets in the blood on the wound surface on the mesh gauze, quickly forming a gel-like black substance and coagulating blood clots, thereby achieving the purpose of hemostasis.
[0004] The main component of the absorbable hemostatic gauze Surgicel used clinically is oxidized regenerated cellulose. It is widely used to control bleeding in surgical operations. It has good biocompatibility and can be completely absorbed in the body. However, Surgicel has weak antibacterial properties and low hemostatic efficiency, and is not suitable for heavy bleeding. Summary of the invention
[0005] In order to improve the problem that the antibacterial property of the hemostatic yarn is weak and the hemostatic efficiency is low, the present application provides an absorbable hemostatic yarn and a preparation method thereof.
[0006] In a first aspect, the present application provides an absorbable hemostatic gauze, which adopts the following technical solution: An absorbable hemostatic gauze is prepared by alkalizing, acidifying, oxidizing and modifying gauze; The modified raw materials include: modified seaweed fiber, carboxymethyl cellulose, modified talcum powder and deionized water.
[0007] By adopting the above technical scheme, an alkalization treatment is first performed, which can increase the cracks on the fiber surface, improve the reactivity of the fiber, and provide more active sites for subsequent chemical modification. The alkalization treatment can also increase the hydrophilicity of the fiber, improve its water absorption performance, and change the surface properties of the gauze fiber, making it rougher, which is conducive to subsequent acidification, oxidation and modification. The acidification treatment can further change the surface properties of the fiber, and by generating -COOH groups, it provides more active sites for subsequent chemical reactions, which helps to improve the water absorption and biocompatibility of the gauze.
[0008] The gauze after oxidation treatment can cross-link with platelets and calcium ions in the blood, promote the formation of blood clots, and thus accelerate the hemostasis process; in addition, while the oxidation treatment improves the water absorption and hemostasis properties of the gauze, it can also maintain the breaking strength and elongation of the gauze, ensuring that it has sufficient strength and toughness during surgical operations. Finally, after modification, the modified seaweed fiber has high hygroscopicity, can absorb a large amount of wound exudate, accelerate blood coagulation and scab rate, and the Ca in the seaweed fiber 2+ Na in blood + After the replacement, an egg-box structure is generated, which can not only stop bleeding, but also promote wound healing and hinder bacterial invasion, thereby achieving the effect of antibacterial hemostasis. Moreover, after the fiber absorbs the exudate, it expands to form a soft gel, which protects the new delicate tissue and prevents secondary trauma when removing the gauze.
[0009] Carboxymethyl cellulose has high hygroscopicity and hemostatic properties. The high water absorption of carboxymethyl cellulose can absorb a large amount of wound exudate and accelerate blood coagulation. The mixture of carboxymethyl cellulose and seaweed fiber can reduce edema and wound irritation. The combination of the two can improve the breaking strength and toughness of gauze. Modified talcum powder can increase the softness and smoothness of gauze, reduce the friction between gauze and skin, prevent gauze from sticking together during use, improve the comfort of patients during use, and absorb excess moisture around the wound to keep the wound dry, which helps to reduce bacterial growth and promote wound healing. Carboxymethyl cellulose allows modified seaweed fiber and modified talcum powder to adhere to the surface of gauze, further modifying the gauze so that the gauze has better hygroscopicity and hemostatic properties, mechanical properties, biocompatibility and degradability, antibacterial properties and promotion of wound healing.
[0010] In a second aspect, the present application also provides a method for preparing an absorbable hemostatic gauze, comprising the following steps: (1) Alkali treatment: soaking the gauze in a sodium hydroxide solution for 1.5-2 hours at a temperature of 36-38° C. to obtain an alkali-treated gauze; (2) Acidification treatment: immersing the alkali-treated gauze obtained in step (1) in a chloroacetic acid solution for 1-1.3 h at room temperature, and drying to obtain an acid-treated gauze; (3) oxidation treatment: soaking the acid-treated yarn obtained in step (2) in a sodium chlorite solution for 2.5-3 hours at a soaking temperature of 28-30° C. to obtain an oxidation-treated gauze; (4) Modification treatment: soaking the oxidized gauze obtained in step (3) in a modification solution at 40-45° C. for 2-2.5 h, filtering, and drying to obtain an absorbable hemostatic gauze; The raw materials of the modified liquid include: modified seaweed fiber, carboxymethyl cellulose, modified talcum powder and deionized water.
[0011] By adopting the above technical solution, the alkali-treated gauze is first treated with sodium hydroxide solution, and the sodium hydroxide solution reacts with the cellulose in the gauze to increase the hydrophilicity of the cellulose, so that the gauze can absorb wound exudate faster and improve its hygroscopicity and hemostatic properties. Sodium hydroxide treatment can optimize the structure of gauze fibers, improve their breaking strength and toughness, and make them more durable during surgical operations.
[0012] Then, the acid-treated gauze is treated with chloroacetic acid solution, which reacts with the cellulose in the gauze to introduce new chemical groups, further improving the hydrophilicity of the gauze, so that it can better absorb exudate during wound care. The treated gauze has better biocompatibility, reduces irritation to the skin, makes it more comfortable during wound healing, and is more easily biodegraded in the body or environment.
[0013] Then, the gauze is treated with sodium chlorite solution to obtain oxidized gauze. Sodium chlorite has good disinfection and sterilization capabilities, and can effectively kill bacteria, viruses and other microorganisms on the surface and inside of the gauze, improve the hygiene standards of the gauze, prevent damage to the gauze fibers during the disinfection process, and maintain the integrity and mechanical properties of the gauze.
[0014] Finally, the gauze is modified with a modification liquid. The dual hemostatic effects of modified seaweed fiber and sodium carboxymethyl cellulose can significantly shorten the hemostatic time, overcoming the shortcomings of common alginate non-woven dressings, such as single hemostatic mechanism, slow hemostatic speed and limited hemostatic effect. When in contact with blood, the modified seaweed fiber will quickly absorb calcium ions in the blood, form gel, and accelerate blood coagulation, thereby achieving a rapid hemostatic effect.
[0015] The combination of modified seaweed fiber and sodium carboxymethyl cellulose can provide a moist healing environment for the wound, promote cell proliferation and tissue regeneration, and accelerate the wound healing process. The addition of modified talc can improve the touch and comfort of gauze, prevent gauze from sticking, reduce the adhesion between gauze and wound, help keep the wound dry, and indirectly promote wound healing.
[0016] Optionally, in step (2), chloroacetic acid is dissolved in deionized water, an ethanol aqueous solution with a mass fraction of 80-90% is added, and the mixture is stirred evenly to obtain a chloroacetic acid solution.
[0017] By adopting the above technical scheme, the chloroacetic acid solution obtained by mixing chloroacetic acid, deionized water and ethanol has anti-inflammatory properties for gauze treatment, which can help reduce the inflammatory response at the wound site; it also has antibacterial properties, can inhibit bacterial growth and reduce the risk of infection; finally, the treated gauze can promote blood coagulation, help stop bleeding, and accelerate the wound healing process.
[0018] Optionally, after the oxidation treatment in step (3), the mixture is ultrasonically washed using cyclohexane, dispersed in lemon oil and ultrasonically washed for 1-2 hours, and finally immersed in an ethanol aqueous solution and ultrasonically washed for 2-3 hours, dried, and set aside.
[0019] By adopting the above technical solution, after the oxidation treatment, cyclohexane is first used for ultrasonic washing to remove the byproducts and residual oxidants generated during the oxidation process, thereby ensuring the cleanliness of the gauze surface and avoiding affecting subsequent treatment or use. Cyclohexane has good solubility and low polarity, and can effectively dissolve grease, wax and certain organic residues, but has a weak solubility for water-soluble substances.
[0020] Re-dispersed in lemon oil and ultrasonicated, lemon oil has natural antibacterial properties, can inhibit bacterial growth, further clean the gauze, has good cleaning ability, can remove grease and impurities on the surface of the gauze, ensure the cleanliness of the gauze, and provide a clean surface for subsequent processing or use.
[0021] Finally, the gauze was ultrasonicated in an ethanol-water solution to remove the residual cyclohexane and lemon oil to ensure that the gauze was clean, and dried to further ensure that no cyclohexane, lemon oil, and ethanol remained on the gauze.
[0022] Optionally, the method for preparing the modified seaweed fiber comprises the following steps: (1) dispersing the seaweed fibers in a phosphoric acid solution, stirring at 50-55° C. for 1-2 hours, filtering, washing, and drying to obtain pretreated seaweed fibers; (2) dispersing chitosan in an acetic acid solution, stirring evenly, adding nanosilver particles, stirring evenly, to obtain a mixed solution; (3) Dispersing the pretreated seaweed fiber obtained in step (1) in the mixed solution of step (2), stirring at a temperature of 60-65° C. for 1-2 hours, drying, and grinding to obtain modified seaweed fiber.
[0023] By adopting the above technical solution, the seaweed fiber molecular chain contains abundant carboxyl groups, which are mixed with the phosphoric acid solution. The phosphoric acid acts as a cross-linking agent and reacts with the carboxyl groups on the alginate molecules to form a stable cross-linking network, thereby enhancing the mechanical strength and stability of the system, improving the hydrophilicity of the seaweed fiber, and facilitating subsequent mixing with other components.
[0024] Chitosan has antibacterial properties, good biocompatibility and biodegradability. Nanosilver particles have a strong antibacterial effect and can be embedded in the structure of chitosan to enhance the antibacterial properties of the system. Chitosan can also be used as a carrier of nanosilver to prevent its aggregation and improve stability. In subsequent applications in absorbable hemostasis, the amino groups on the chitosan molecules can electrostatically adsorb with negatively charged components in the blood (such as red blood cells and platelets), promote platelet aggregation and activation, and achieve rapid hemostasis; the combination of chitosan and fibrin enhances the structural stability of the thrombus and improves the efficiency of hemostasis. At the same time, the porous structure of chitosan helps absorb wound exudate, keep the wound dry, and promote healing.
[0025] The pretreated seaweed fiber is dispersed in a chitosan mixture, and the nanosilver particles can also be loaded on the surface of the seaweed fiber. The seaweed fiber is embedded in the chitosan structure, which improves the hemostatic, antibacterial and mechanical properties of the system. It is subsequently applied to hemostatic gauze. The modified seaweed fiber adheres to the surface of the gauze, which can not only stop bleeding quickly, but also has the advantages of antibacterial, promoting wound healing, biocompatibility and biodegradability.
[0026] Optionally, the mass ratio of the seaweed fiber, chitosan and nano-silver particles is 1:0.7-0.8:0.2-0.3.
[0027] By adopting the above technical scheme, the mass ratio of seaweed fiber, chitosan and nano-silver particles is further limited within a certain range, and the comprehensive performance of modified seaweed fiber is improved. Seaweed fiber is mainly composed of alginic acid, which can absorb a large amount of water and form a gel, which helps blood coagulation and accelerates the hemostasis process; chitosan interacts with negatively charged components in the blood (such as platelets) through its positive charge, promotes platelet aggregation and accelerates the coagulation process; the antibacterial properties of nano-silver particles can prevent wound infection and indirectly promote hemostasis and healing. Nano-silver particles can also be loaded on the surface of seaweed fiber, and seaweed fiber is embedded in the chitosan structure. The combination of the three not only improves the hemostasis efficiency, but also enhances the antibacterial properties and promotes wound healing, while maintaining good biocompatibility and biodegradability.
[0028] Optionally, the preparation method of the modified talcum powder comprises the following steps: (1) calcining talc at 400-420° C. for 2-3 h, dispersing the talc in anhydrous ethanol, stirring for 1-2 h, filtering, and drying to obtain pretreated talc; (2) dispersing the carbon nanotubes in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, stirring evenly, performing azeotropic reflux, filtering, washing and drying to obtain pretreated carbon nanotubes; (3) Dispersing the pretreated talc powder of step (1) in deionized water, adding the pretreated carbon nanotubes and xanthan gum of step (2), stirring at a temperature of 70-75° C. for 2-3 h, filtering, and drying to obtain modified talc powder.
[0029] By adopting the above technical solution, talcum powder is first calcined to remove organic impurities and some inorganic impurities in talcum powder, improve its whiteness and purity, and facilitate subsequent mixing with other components. Pre-treating carbon nanotubes with concentrated acid can acidify carbon nanotubes to form functional groups such as carboxyl, improve the chemical activity, purity and dispersibility of carbon nanotubes, and make them less likely to agglomerate.
[0030] Pretreated talcum powder is dispersed in deionized water, and pretreated carbon nanotubes and xanthan gum are added. Carbon nanotubes can be loaded on the surface and pores of talcum powder. Xanthan gum has viscosity, so that carbon nanotubes can be stably loaded in the talcum powder structure, thereby improving the mechanical properties of talcum powder. When applied to hemostatic gauze, the addition of talcum powder can improve the wear resistance and tensile strength of the gauze. Carbon nanotubes have extremely high strength and toughness, and can significantly enhance the mechanical properties of gauze, improve its tear resistance and tension resistance. Xanthan gum can not only improve the compatibility of gauze with skin, reduce irritation and allergic reactions, but also make talcum powder and carbon nanotubes adhere tightly, thereby improving the stability of subsequent gauze modification. The combination of the three can also form a protective gel layer to keep the wound moist, promote cell proliferation and healing, promote cell adhesion and proliferation, and also have certain antibacterial properties, which helps prevent wound infection.
[0031] Optionally, the mass ratio of the talcum powder, the carbon nanotubes and the xanthan gum is 1:0.3-0.5:0.1-0.2.
[0032] By adopting the above technical scheme, the mass ratio of talcum powder, carbon nanotubes and xanthan gum is further limited within a certain range, thereby improving the comprehensive performance of talcum powder. Carbon nanotubes have good mechanical properties and antibacterial properties and can be loaded on the surface and pores of talcum powder to improve the mechanical properties of talcum powder and promote wound healing. Xanthan gum makes talcum powder and carbon nanotubes adhere tightly. The modified talcum powder is used in hemostatic gauze, which not only improves the mechanical properties and biocompatibility of the gauze, but also enhances its antibacterial properties and promotes wound healing.
[0033] Optionally, the gauze is prepared by regenerating oxidized cellulose fibers, and the structural forms of the gauze include woven type and non-woven filament type.
[0034] Further preferably, the woven weight is: 80-160g / m 2 , non-woven filament type weight: 50-250g / m 2 .
[0035] By adopting the above technical solution, the structural form of the gauze is limited, and the obtained gauze has good strength, air permeability, absorption performance and biocompatibility, reducing the risk of wound infection and improving the comfort of patients; the absorption performance of the gauze is optimized so that it can more effectively absorb exudate when treating wounds and promote wound healing.
[0036] Optionally, the thickness of the gauze is 0.15-0.17 mm; the unit weight of the gauze is 50-250 g / m 2 .
[0037] By adopting the above technical solution, the thickness and unit weight of the gauze are limited, and the obtained gauze has good strength and stability, while maintaining appropriate air permeability and softness, thereby improving the comfort of patients.
[0038] In summary, this application has the following beneficial effects: 1. In this application, alkalization treatment is first performed to improve the reactivity of the fiber and provide more active sites for subsequent chemical modification. Alkalization treatment can also increase the hydrophilicity of the fiber and change the surface properties of the gauze fiber, making it rougher, which is conducive to subsequent acidification, oxidation and modification treatment. Acidification treatment can further change the surface properties of the fiber and help improve the water absorption and biocompatibility of the gauze by generating -COOH groups.
[0039] 2. The gauze after oxidation treatment in this application can cross-link with platelets and calcium ions in the blood, promote the formation of blood clots, and thus accelerate the hemostasis process. After modification, the modified seaweed fiber has high hygroscopicity, can absorb a large amount of wound exudate, accelerate blood coagulation and scab formation rate, and achieve the effect of antibacterial hemostasis.
[0040] 3. In the present application, carboxymethyl cellulose allows modified seaweed fiber and modified talc to adhere to the surface of gauze, further modifying the gauze so that the gauze has better hygroscopicity and hemostatic properties, mechanical properties, biocompatibility and degradability, antibacterial properties and promotes wound healing. DETAILED DESCRIPTION
[0041] Preparation example of modified seaweed fiber Preparation Example 1-1 The preparation method of modified seaweed fiber comprises the following steps: (1) dispersing 1.2 kg of seaweed fiber in 2 L of 30% by mass phosphoric acid solution, stirring at 55° C. for 1.5 h, filtering, washing, and drying to obtain pretreated seaweed fiber; (2) dispersing chitosan in 2 L of 10% by mass acetic acid solution, stirring evenly, adding nanosilver particles, stirring evenly, and obtaining a mixed solution; (3) Dispersing the pretreated seaweed fiber obtained in step (1) in the mixed solution of step (2), stirring at a temperature of 65° C. for 2 h, drying, and grinding to obtain modified seaweed fiber.
[0042] The mass ratio of seaweed fiber, chitosan and nanosilver particles is 1:0.7:0.2.
[0043] Preparation Example 1-2 The difference from Preparation Example 1-1 is that in step (2), chitosan is not added.
[0044] Preparation Example 1-3 The difference from Preparation Example 1-1 is that in step (2), no nanosilver particles are added.
[0045] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of seaweed fiber, chitosan and nano-silver particles is 1:0.8:0.3.
[0046] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of seaweed fiber, chitosan and nano-silver particles is 1:0.1:0.6.
[0047] Preparation example of modified talc Preparation Example 2-1 The preparation method of modified talcum powder comprises the following steps: (1) 1.1 kg of talc was calcined at 420° C. for 3 h, then dispersed in 2 L of anhydrous ethanol, stirred for 2 h, filtered, and dried to obtain pretreated talc; (2) dispersing the carbon nanotubes in a mixed solution of 2 L of concentrated sulfuric acid and concentrated nitric acid, stirring evenly, performing azeotropic reflux, filtering, washing and drying to obtain pretreated carbon nanotubes; (3) The pretreated talc powder of step (1) was dispersed in 3 L of deionized water, and the pretreated carbon nanotubes and xanthan gum of step (2) were added, stirred at 75° C. for 3 h, filtered, and dried to obtain modified talc powder.
[0048] Mixed solution of concentrated sulfuric acid and concentrated nitric acid: Concentrated sulfuric acid and concentrated nitric acid are mixed in a volume ratio of 1:1 to form a mixed acid solution, in which the mass fraction of concentrated sulfuric acid is 95% and the mass fraction of concentrated nitric acid is 65%.
[0049] The reflux temperature of the reflux treatment was 100° C. and the duration was 3 h.
[0050] The mass ratio of talc, carbon nanotubes and xanthan gum is 1:0.3:0.1.
[0051] Preparation Example 2-2 The difference from Preparation Example 2-1 is that in step (2), no carbon nanotubes are added.
[0052] Preparation Example 2-3 The difference from Preparation Example 2-1 is that in step (3), no xanthan gum is added.
[0053] Preparation Example 2-4 The difference from Preparation Example 2-1 is that the mass ratio of talcum powder, carbon nanotubes and xanthan gum is 1:0.5:0.2.
[0054] Preparation Example 2-5 The difference from Preparation Example 2-1 is that the mass ratio of talcum powder, carbon nanotubes and xanthan gum is 1:0.1:0.6. Example
[0055] Example 1 An absorbable hemostatic gauze is prepared by alkalizing, acidifying, oxidizing and modifying gauze; Specifically, the preparation method of absorbable hemostatic gauze comprises the following steps: (1) Alkali treatment: 1 kg of gauze was immersed in 2 L of 35% sodium hydroxide solution for 2 h at a temperature of 38° C. to obtain alkali-treated gauze; (2) Acidification treatment: immersing the alkali-treated gauze obtained in step (1) in a chloroacetic acid solution at room temperature for 1.3 h, and drying to obtain an acid-treated gauze; (3) oxidation treatment: the acid-treated yarn obtained in step (2) is immersed in 3 L of 20% sodium chlorite solution at a temperature of 30° C. for 3 h to obtain an oxidation-treated gauze; (4) Modification treatment: soaking the oxidized gauze obtained in step (3) in a modification solution at 45° C. for 2.5 h, filtering, and drying to obtain an absorbable hemostatic gauze; The raw materials of the modified liquid include: 1 kg modified seaweed fiber, 0.2 kg carboxymethyl cellulose, 0.8 kg modified talcum powder, and 3 kg deionized water. The various raw materials are mixed evenly to obtain the modified liquid.
[0056] In step (2), 2 kg of chloroacetic acid (purchased from Zibo Anhao Chemical Co., Ltd.) was dissolved in 4 L of deionized water, 1 L of 90% ethanol aqueous solution was added, and the mixture was stirred evenly to obtain a chloroacetic acid solution.
[0057] After the oxidation treatment in step (3), the mixture was ultrasonically washed using 5 L of cyclohexane, dispersed in 4 L of lemon oil and ultrasonically washed for 1 h, and finally immersed in 4 L of 95% ethanol aqueous solution and ultrasonically washed for 2 h, dried, and set aside.
[0058] The gauze is woven from regenerated oxidized cellulose fibers, and the regenerated oxidized cellulose fibers are prepared by wet spinning regenerated oxidized cellulose (purchased from Qingdao Zhongteng Biotechnology Co., Ltd.); 1 kg of regenerated oxidized cellulose is dispersed in a copper ammonia solution to obtain a spinning solution, the mass concentration of the spinning solution is 18%, and the spinning solution is extruded through a spinneret to prepare the regenerated oxidized cellulose fibers.
[0059] Wet spinning process parameters: spinneret specification is 21000 holes × 0.06mm, spinning speed is 55m / min, coagulation bath temperature is 52°C, plasticizing bath temperature is 95°C, coagulation bath composition is: sulfuric acid 115g / L, sodium sulfate 325g / L, zinc sulfate 11.5g / L.
[0060] The regenerated oxidized cellulose fibers are woven into gauze to obtain a woven gauze, and the weaving parameters are: a warp yarn density of 50 yarns / cm and a weft yarn density of 30 yarns / cm.
[0061] The thickness of the gauze is 0.15mm; the unit weight of the gauze is 100g / m 2 .
[0062] The modified seaweed fiber was prepared in Preparation Example 1-1, and the modified talc was prepared in Preparation Example 2-1.
[0063] Example 2 An absorbable hemostatic gauze, which is different from embodiment 1 in that it comprises the following steps: (1) Alkali treatment: 1.2 kg of gauze was immersed in a sodium hydroxide solution with a mass fraction of 37% for 1.5 h at a temperature of 36° C. to obtain alkali-treated gauze; (2) Acidification treatment: immersing the alkali-treated gauze obtained in step (1) in a chloroacetic acid solution for 1 hour at room temperature, and drying to obtain an acid-treated gauze; (3) Oxidation treatment: the acid-treated yarn obtained in step (2) was immersed in 3 L of 10% sodium chlorite solution at a temperature of 28° C. for 2.5 h to obtain an oxidized gauze; (4) Modification treatment: soak the oxidized gauze obtained in step (3) in a modification solution at 40° C. for 2 h, filter, and dry to obtain absorbable hemostatic gauze; in step (2), dissolve 2 kg of chloroacetic acid in 4 L of deionized water, add 1 L of 80% ethanol aqueous solution, stir evenly, and obtain a chloroacetic acid solution.
[0064] After the oxidation treatment in step (3), the mixture was ultrasonically washed using 5 L of cyclohexane, dispersed in 4 L of lemon oil and ultrasonically washed for 2 h, and finally immersed in 4 L of 95% ethanol aqueous solution and ultrasonically washed for 3 h, dried, and set aside.
[0065] The regenerated oxidized cellulose fibers are made into gauze to obtain non-woven filament gauze. The regenerated oxidized cellulose fibers are randomly laid on a mesh belt running forward under the airflow dispersion of a filament separator to form a fiber web, and then hot-rolled and bonded to obtain a non-woven filament gauze. The speed of air flow dispersion was controlled at 4500 m / min, and during hot rolling bonding, the temperature of the hot pressing roller was 135°C, the pressure of the hot pressing roller was 6 MPa, and the rolling mill speed was 31 rpm. The thickness of the gauze is 0.17mm; the unit weight of the gauze is 200g / m 2 .
[0066] Example 3 An absorbable hemostatic gauze is different from Example 1 in that the cyclohexane and lemon oil ultrasonic treatment is not performed.
[0067] Example 4 An absorbable hemostatic gauze, which is different from Example 1 in that the modified seaweed fiber adopts Preparation Example 1-2.
[0068] Example 5 An absorbable hemostatic gauze, which is different from Example 1 in that the modified seaweed fiber adopts Preparation Example 1-3.
[0069] Example 6 An absorbable hemostatic gauze, which is different from Example 1 in that the modified seaweed fiber adopts Preparation Example 1-4.
[0070] Example 7 An absorbable hemostatic gauze, which is different from Example 1 in that the modified seaweed fiber is prepared as in Preparation Example 1-5.
[0071] Example 8 An absorbable hemostatic gauze, which is different from Example 1 in that the modified talcum powder adopts the preparation example 2-2.
[0072] Example 9 An absorbable hemostatic gauze, which is different from Example 1 in that the modified talcum powder adopts the preparation example 2-3.
[0073] Example 10 An absorbable hemostatic gauze, which is different from Example 1 in that the modified talcum powder adopts Preparation Example 2-4.
[0074] Embodiment 11 An absorbable hemostatic gauze, which is different from Example 1 in that the modified talcum powder adopts Preparation Example 2-5.
[0075] Comparative Example Comparative Example 1 An absorbable hemostatic gauze, which is different from Example 1 in that modified seaweed fiber is not added.
[0076] Comparative Example 2 An absorbable hemostatic gauze, which is different from Example 1 in that the modified seaweed fiber is replaced by an equal amount of seaweed fiber.
[0077] Comparative Example 3 An absorbable hemostatic gauze, which is different from Example 1 in that modified talcum powder is not added.
[0078] Comparative Example 4 An absorbable hemostatic gauze, which is different from Example 1 in that an equal amount of talc is used to replace the modified talc.
[0079] Performance testing The absorbable hemostatic yarns prepared in Examples 1-11 and Comparative Examples 1-4 were subjected to performance tests.
[0080] 1. The absorbable hemostatic gauze of Examples 1-11 and Comparative Examples 1-4 was cut into 3 cm × 3 cm pieces. 60 purebred New Zealand white rabbits, half of which were male and half were female, with a body weight range of 2.55 ± 0.05 kg, were randomly divided into 15 groups, with 4 rabbits in each group, half of which were male and half were female. 3% sodium pentobarbital solution was slowly injected into the ear vein after disinfection, and the experiment was carried out after the rabbits were completely anesthetized; The back of a purebred New Zealand white rabbit was trimmed to an area of about 5 cm×5 cm. After disinfection, the full layer of skin was cut transversely with surgical scissors at 2 cm on both sides of the back spine to form a 2 cm×2 cm full-thickness skin defect bleeding ulcer wound model (one on each side of each rabbit). The absorbable hemostatic gauze of the embodiment was quickly applied to the bleeding ulcer wound, and ordinary sterilized gauze was intermittently used to clean the wound exudate, and then the hemostatic effect was observed and the hemostatic time was recorded, and the hemostatic time of each group was averaged.
[0081] 2. The absorbable hemostatic gauze of Examples 1-11 and Comparative Examples 1-4 was cut into 1 cm×1 cm pieces. 60 purebred New Zealand white rabbits, half of which were male and half were female, with a body weight range of 2.55±0.05 kg, were randomly divided into 15 groups, with 4 rabbits in each group, half of which were male and half were female. 3% sodium pentobarbital solution was slowly injected into the ear vein after disinfection, and the experiment was carried out after the rabbits were completely anesthetized; The position near the femoral vein was disinfected with iodine tincture, and then a 0.9 cm wound was made with a scalpel, and the absorbable hemostatic gauze of the embodiment was quickly stuffed into the wound, and the blood oozing from the wound was cleaned with ordinary sterilized gauze, and then the wound was sutured, the wound was observed and the stitches were removed on the 7th day after the operation, and the remaining amount of each absorbable hemostatic gauze was recorded and averaged, and the degradation time was recorded; 3. The absorbent hemostatic gauze of Examples 1-11 and Comparative Examples 1-4 was tested for liquid absorption rate, tensile strength and antibacterial performance, wherein the test method for liquid absorption rate was in accordance with Part 1 of YY / T 0471.1-2004, the test method for tensile strength was in accordance with Part 3 of GB / T24218.3-2010, and the test method for antibacterial performance was in accordance with Part 2 of GB / T14233.2-2005. The test results are shown in Table 1.
[0082] Table 1 Test data of embodiments and comparative examples Combining the data in the examples and Table 1, it can be seen that the absorbable hemostatic gauze made in Examples 1-2 has good hemostatic efficiency, mechanical properties, antibacterial rate and degradation efficiency. Among them, the average hemostatic time of Example 1 is 97±5s, the absorbable hemostatic gauze is completely absorbed, the degradation time is 7.0±0.1 days, the liquid absorption speed is 97g / g, the tensile strength is 8.96cN / dtex, and the antibacterial rate is 100%. It shows that the gauze of the present application is made by alkalization, acidification, oxidation and modification, which can not only stop bleeding, but also has antibacterial effect and high hemostatic efficiency.
[0083] After the oxidation treatment in Example 3, the gauze was not cleaned and was directly modified. As shown in Table 1, the average hemostasis time and degradation time of Example 3 were prolonged, the liquid absorption speed, tensile strength and antibacterial rate were decreased, and the average residual was 0.3 mm 2 , indicating that after oxidation treatment, cyclohexane, lemon oil, and ethanol are used to clean the gauze to remove grease and impurities on the surface of the gauze, ensure the cleanliness of the gauze, and provide a clean surface for subsequent treatment or use.
[0084] Chitosan is not added in the modified seaweed fiber preparation method of Example 4, and nanosilver particles are not added in the modified seaweed fiber preparation method of Example 5. The mass ratio of seaweed fiber, chitosan and nanosilver particles is changed in Examples 6-7. As can be seen from Table 1, compared with Example 1, the average hemostasis time and degradation time of Examples 4-5 are prolonged, the liquid absorption speed, tensile strength and antibacterial rate are reduced, and the average surplus is significantly increased. The average hemostasis time, degradation time and average surplus of Example 7 are reduced compared with Examples 3-4, but longer than Examples 1-2 and Example 4. The liquid absorption speed, tensile strength and antibacterial rate are greater than those of Examples 4-5, but less than those of Examples 1-2 and Example 4, indicating that nanosilver particles can also be loaded on the surface of seaweed fibers, and seaweed fibers are embedded in the chitosan structure. The combination of the three not only improves the hemostasis efficiency, but also enhances the antibacterial property, promotes wound healing, and maintains good biocompatibility and biodegradability.
[0085] In the preparation method of the modified talc powder of Example 8, no carbon nanotubes are added, and in the preparation method of the modified talc powder of Example 9, no xanthan gum is added. In Examples 10-11, the mass ratio of talc powder, carbon nanotubes and xanthan gum is changed. As can be seen from Table 1, compared with Example 1, the average hemostasis time and degradation time of Examples 8-9 are prolonged, the liquid absorption speed, tensile strength and antibacterial rate are decreased, and the average surplus is significantly increased. The average hemostasis time, degradation time and average surplus of Example 11 are reduced compared with Examples 8-9, but longer than Examples 1-2 and Example 10, and the liquid absorption speed, tensile strength and antibacterial rate are greater than Examples 8-9, but less than Examples 1-2 and Example 4, indicating that Comparative Example 1 does not add modified seaweed fiber, and Comparative Example 3 does not add modified talcum powder. As can be seen from Table 1, compared with Example 1, the average hemostasis time and degradation time of Comparative Examples 1 and 3 are prolonged, the average margin is significantly increased, and the liquid absorption speed, tensile strength, and antibacterial rate are all decreased, indicating that the modified seaweed fiber of the present application absorbs a large amount of wound exudate, accelerates blood coagulation and scab formation rate, and the modified talcum powder reduces the friction between the gauze and the skin, prevents the gauze from sticking together during use, helps to reduce bacterial growth, and promotes wound healing.
[0086] Comparative Example 2 and Comparative Example 4 respectively replace the modified seaweed fiber with an equal amount of seaweed fiber and replace the modified talc with an equal amount of talc. As can be seen from Table 1, compared with Example 1, the average hemostasis time and degradation time of Comparative Examples 2 and 4 are prolonged, the average margin is significantly increased, the liquid absorption speed, tensile strength and antibacterial rate are all decreased, but the comprehensive performance is better than that of Comparative Example 1 and Comparative Example 3, indicating that the modified seaweed fiber and talc in the present application have excellent hemostatic, antibacterial and mechanical properties, promote wound healing, and hinder bacterial invasion, thereby achieving the effect of antibacterial hemostasis.
[0087] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An absorbable hemostatic gauze, characterized in that: It is made of gauze through alkalization, acidification, oxidation and modification treatment; The modified raw materials include: modified seaweed fiber, carboxymethyl cellulose, modified talcum powder and deionized water.
2. The method for preparing an absorbable hemostatic gauze according to claim 1, characterized in that: The steps include: (1) Alkali treatment: soak the gauze in a sodium hydroxide solution for 1.5-2 hours at a temperature of 36-38°C to obtain alkali-treated gauze; (2) Acidification treatment: immersing the alkali-treated gauze obtained in step (1) in a chloroacetic acid solution at room temperature for 1-1.3 hours, and drying to obtain an acid-treated gauze; (3) Oxidation treatment: soak the acid-treated yarn obtained in step (2) in a sodium chlorite solution for 2.5-3 hours at a soaking temperature of 28-30° C. to obtain an oxidized gauze; (4) Modification treatment: soaking the oxidized gauze obtained in step (3) in a modification solution at 40-45° C. for 2-2.5 h, filtering, and drying to obtain an absorbable hemostatic gauze; The raw materials of the modified liquid include: modified seaweed fiber, carboxymethyl cellulose, modified talcum powder and deionized water.
3. The method for preparing an absorbable hemostatic gauze according to claim 2, characterized in that: In step (2), chloroacetic acid is dissolved in deionized water, and an ethanol aqueous solution with a mass fraction of 80-90% is added and stirred evenly to obtain a chloroacetic acid solution.
4. The method for preparing an absorbable hemostatic gauze according to claim 2, characterized in that: After the oxidation treatment in step (3), the mixture is ultrasonically washed using cyclohexane, dispersed in lemon oil and ultrasonically washed for 1-2 hours, and finally immersed in an ethanol aqueous solution and ultrasonically washed for 2-3 hours, and then dried for later use.
5. The absorbable hemostatic gauze according to claim 1, characterized in that: The preparation method of the modified seaweed fiber comprises the following steps: (1) dispersing the seaweed fiber in a phosphoric acid solution, stirring at 50-55° C. for 1-2 hours, filtering, washing, and drying to obtain pretreated seaweed fiber; (2) dispersing chitosan in acetic acid solution, stirring evenly, adding nanosilver particles, stirring evenly to obtain a mixed solution; (3) Dispersing the pretreated seaweed fiber obtained in step (1) in the mixed solution of step (2), stirring at a temperature of 60-65° C. for 1-2 h, drying, and grinding to obtain modified seaweed fiber.
6. The absorbable hemostatic gauze according to claim 5, characterized in that: The mass ratio of the seaweed fiber, chitosan and nano-silver particles is 1:0.7-0.8:0.2-0.
3.
7. The absorbable hemostatic gauze according to claim 1, characterized in that: The preparation method of the modified talcum powder comprises the following steps: (1) calcining talc at 400-420°C for 2-3h, dispersing it in anhydrous ethanol, stirring it for 1-2h, filtering it, and drying it to obtain pretreated talc; (2) dispersing the carbon nanotubes in a mixed solution of concentrated sulfuric acid and concentrated nitric acid, stirring evenly, performing azeotropic reflux, filtering, washing and drying to obtain pretreated carbon nanotubes; (3) Dispersing the pretreated talc powder of step (1) in deionized water, adding the pretreated carbon nanotubes and xanthan gum of step (2), stirring at a temperature of 70-75° C. for 2-3 h, filtering, and drying to obtain modified talc powder.
8. The absorbable hemostatic gauze according to claim 7, characterized in that: The mass ratio of the talcum powder, the carbon nanotubes and the xanthan gum is 1:0.3-0.5:0.1-0.
2.
9. The absorbable hemostatic gauze according to claim 1, characterized in that: The gauze is prepared by regenerating oxidized cellulose fibers, and the structural forms of the gauze include a woven type and a non-woven filament type.
10. The absorbable hemostatic gauze according to claim 1, characterized in that: The thickness of the gauze is 0.15-0.17 mm; the unit weight of the gauze is 50-250 g / m 2 .